2021
DOI: 10.3389/fnins.2021.642589
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging of the Sciatic Nerve as a Surrogate Marker for Nerve Functionality of the Upper and Lower Limb in Patients With Diabetes and Prediabetes

Abstract: BackgroundNerve damage in diabetic neuropathy (DN) is assumed to begin in the distal legs with a subsequent progression to hands and arms at later stages. In contrast, recent studies have found that lower limb nerve lesions in DN predominate at the proximal sciatic nerve and that, in the upper limb, nerve functions can be impaired at early stages of DN.Materials and MethodsIn this prospective, single-center cross-sectional study, participants underwent diffusion-weighted 3 Tesla magnetic resonance neurography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 34 publications
4
34
1
2
Order By: Relevance
“…The assessment of multiple nerves, as mentioned above, especially motor nerves (e.g., femoral nerve) could provide even more specific results. The healthy controls tended to be of slightly younger age compared to the patients without revealing significant relevance; however, this needs to be considered as some studies showed that FA of the sciatic nerve is negatively associated with age in both healthy controls and patients with neuropathies (Kronlage et al, 2018;Jende et al, 2021). Of note, there was no significant correlation between age and FA values in our study cohort.…”
Section: Figure 2 | (A)contrasting
confidence: 60%
See 2 more Smart Citations
“…The assessment of multiple nerves, as mentioned above, especially motor nerves (e.g., femoral nerve) could provide even more specific results. The healthy controls tended to be of slightly younger age compared to the patients without revealing significant relevance; however, this needs to be considered as some studies showed that FA of the sciatic nerve is negatively associated with age in both healthy controls and patients with neuropathies (Kronlage et al, 2018;Jende et al, 2021). Of note, there was no significant correlation between age and FA values in our study cohort.…”
Section: Figure 2 | (A)contrasting
confidence: 60%
“…Our main findings are that ALS patients' sciatic nerves demonstrate significantly lower FA values than healthy controls, and the thigh muscles in ALS patients accumulate more fat than thigh muscles from healthy controls. Although DTI derived FA in rodent (Takagi et al, 2009;Lehmann et al, 2010;Morisaki et al, 2011) and human peripheral nerves is considered a valid measure for axonal integrity and can be used to monitor axonal loss and regeneration as well as for demyelinating conditions (Sheikh, 2010;Kakuda et al, 2011;Mathys et al, 2013;Jende et al, 2020Jende et al, , 2021, data about FA values in peripheral nerves of ALS patients are sparse. In line with our findings, Simon and colleagues reported 8-10% lower FA values in the tibial and peroneal nerves in ALS patients than controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar blood-flow measures are unlikely to be of value in nerve imaging. That is not, however, to say that measures will not be able to be developed which probe the ability of nerves to function, and we refer readers to the paper in this edition by Jende et al ( 2021 ), exploring DTI as a surrogate measure of nerve function.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies on diabetes consider peripheral sensorimotor neuropathy of the lower extremities, and only a few, mostly sensory and motor nerve conduction velocity studies have examined sensory function in the hands (57)(58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%